Designed inhibitor for nuclear localization signal of polo‐like kinase 1 induces mitotic arrest. (24th November 2016) - Chen, Fangjin; Zhuo, Xiaolong; Qin, Tan; Guo, Xiao; Zhang, Chuanmao; Lai, Luhua
Abstract : Polo‐like kinase 1 (Plk1), a member of polo‐like kinase family, regulates multiple essential steps of the cell cycle progression. Plk1 is overexpressed in multiple cancer cell lines and considered to be a prime anticancer target. Plk1 accumulates in the nucleus during S and G2 phases by its bipartite nuclear localization signal (NLS) sequence, which is crucial for Plk1 regulation during normal cell cycle progression. Here, through combined computational and experimental studies, we identified compound D110, which inhibits Plk1 kinase activity with an IC50 of 85 nm and blocks the nuclear localization of Plk1 during S and G2 phases. D110‐treated cancer cells were arrested at mitosis with monopolar spindle, indicating the inhibition of the Plk1 kinase activity in cell. As D110 interacts with both the ATP site and the NLS in Plk1, it demonstrates good selectivity toward Plk2 and Plk3. The strategy of simultaneously inhibiting kinase activity and its subcellular translocations offers a novel approach for selective kinase inhibitor design. Abstract : Inhibitor target the nuclear localization signal (NLS) of polo‐like kinase 1 (Plk1) was rationally designed through virtual screening. The NLS inhibitor D110 strongly inhibits the activity of Plk1 with the IC50 of 85 nm . D110 inhibits the translocation of Plk1 into nucleus in HeLa cells during interphase.